Self-soothing behaviors with particular reference to oxytocin release induced by non-noxious sensory stimulation - Uvnäs-Moberg, Kerstin; Handlin, Linda; Petersson, Maria (Frontiers in Psychology, 2015)
Oxytocin, a hypothalamic nonapeptide, is linked to increased levels of social interaction, well-being and anti-stress effects. The effects of oxytocin that is released by sensory stimulation during different kinds of interactive behaviors are often underestimated or even forgotten. In fact, many of the positive effects caused during interaction, such a wellbeing, stress reduction and even health promotion, are indeed linked to oxytocin released in response to activation of various types of sensory nerves. Oxytocin is released in response to activation of sensory nerves during labor, breastfeeding and sexual activity. In addition oxytocin is released in response to low intensity stimulation of the skin, e.g. in response to touch, stroking, warm temperature etc . Consequently oxytocin is not only released during interaction between mothers and infants, but also during positive interaction between adult or between humans and animals. Finally oxytocin is also released in response to suckling and food intake. Oxytocin released in the brain in response to sensory stimulation as a consequence of these types of interactive behaviors, contributes to every day wellbeing and ability to handle stress. Food intake or sex may be used or even abused to achieve oxytocin-linked wellbeing and stress relief to compensate for lack of good relationships or when the levels of anxiety are high. The present review article will summarize the role played by oxytocin released by sensory (in particular somatosensory) stimulation, during various kinds of interactive behaviors. Also the fact that the anti-stress effects of oxytocin are particularly strong when oxytocin is released in response to “low intensity” stimulation of the skin will be highlighted.